Let the investments of A, B, and C be represented as \( a \), \( b \), and \( c \) respectively.
The problem gives the following relationships:
\[
2a = 3b \quad \text{(Twice A's investment is equal to thrice B's investment)}
\]
\[
b = 4c \quad \text{(B's investment is four times C's investment)}
\]
Step 1: Express \( a \) and \( b \) in terms of \( c \):
From \( b = 4c \), we substitute this into \( 2a = 3b \):
\[
2a = 3 \times 4c = 12c \quad \Rightarrow \quad a = 6c.
\]
Step 2: Now, the total investment is \( a + b + c \):
\[
a + b + c = 6c + 4c + c = 11c.
\]
Step 3: The total profit is ₹ 49500, and the share of each partner is proportional to their investment.
Thus, B's share in the profit is:
\[
\frac{b}{a + b + c} \times 49500 = \frac{4c}{11c} \times 49500 = \frac{4}{11} \times 49500 = ₹ 18,000.
\]